Constable,Robert. “Family education and family therapy: tools for relational change” . ESE. Estudios sobre educación. 2004, Nº 6, PÁG.9-26 - Robert Constable (Estudios sobre Educación, 2004)
In this paper, I wish to outline the substantive base for family education and family therapy in the necessary interaction of family members to secure uniquely human needs –to create a secure and safe base, to belong, to communicate, to have choices within an ethical, relational framework, to grow, to interact, to care for others and to love. Family interaction, if it is successful, creates the context for human development and human care of vulnerable persons –all of us. I will use these reflections on the substance of family interaction briefly to discuss family therapy and family education and raise questions for further work in this area.